2020
DOI: 10.1186/s13054-020-2761-6
|View full text |Cite
|
Sign up to set email alerts
|

Assisted mechanical ventilation promotes recovery of diaphragmatic thickness in critically ill patients: a prospective observational study

Abstract: Background: Diaphragm atrophy and dysfunction are consequences of mechanical ventilation and are determinants of clinical outcomes. We hypothesize that partial preservation of diaphragm function, such as during assisted modes of ventilation, will restore diaphragm thickness. We also aim to correlate the changes in diaphragm thickness and function to outcomes and clinical factors. Methods: This is a prospective, multicentre, observational study. Patients mechanically ventilated for more than 48 h in controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…Diaphragm biopsies from ICU patients also demonstrated a reduction in active and passive diaphragm myofibrillar force and reduced cross-sectional area of slow-twitch and fast-twitch fibers as compared with control values [ 9 11 ]. Importantly, maintaining diaphragm activity under mechanical ventilation has been shown to be protective [ 12 , 13 ]. Changes in diaphragm thickness were correlated with the amount of inactivity and are associated with complications of mechanical ventilation and a poor outcome [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diaphragm biopsies from ICU patients also demonstrated a reduction in active and passive diaphragm myofibrillar force and reduced cross-sectional area of slow-twitch and fast-twitch fibers as compared with control values [ 9 11 ]. Importantly, maintaining diaphragm activity under mechanical ventilation has been shown to be protective [ 12 , 13 ]. Changes in diaphragm thickness were correlated with the amount of inactivity and are associated with complications of mechanical ventilation and a poor outcome [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, maintaining diaphragm activity under mechanical ventilation has been shown to be protective [ 12 , 13 ]. Changes in diaphragm thickness were correlated with the amount of inactivity and are associated with complications of mechanical ventilation and a poor outcome [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…While development of, and risk factors for, ventilator-induced diaphragmatic weakness are well described [ 29 31 ], little is known about potential reversibility. In a physiological study, Grassi and co-workers demonstrated a correlation between mode of ventilation and changes in diaphragmatic thickness [ 32 ]. After early thinning during a short period of controlled ventilation, thickness and thickening fraction recuperated in about 50% of patients within one week after switching to assisted ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…While diaphragm atrophy is widely described in the recent literature, the reversal of this process is still poorly studied. Nevertheless, Grassi et al [37] in a prospective multicentre study demonstrated that pressure support mode can lead to partial restoration of Diaphragm thickness.…”
Section: Discussionmentioning
confidence: 99%